2017
DOI: 10.1002/ejlt.201600316
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysical properties of different olive oils: Evaluating density and rheology through a fluid dynamic approach

Abstract: The aim of this study was to investigate the Newtonian viscosity and density of different types of olive oils with the ultimate aim of optimizing the unit operations involved in their production process. A total of 14 oils were selected and tested at a wide range of temperatures. These included ten extra virgin olive oils (EVOOs) and four olive oils (OOs) from five different countries of origin. The oils were analyzed to determine their fatty acid (FA) composition and all were found to contain large amounts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
2
2
0
Order By: Relevance
“…Newtonian viscosity presented close values to the ones published by Santos et al (2005) for different vegetable oils. In the same way, the viscosity of buriti oil was comparable to the values found by Ribeiro et al (2017) for different commercial olive oils. These olive oils had a very similar fatty acid composition to buriti oil, which also resulted in close agreement between buriti and olive oil densities.…”
Section: Physicochemical and Thermophysical Analysessupporting
confidence: 84%
“…Newtonian viscosity presented close values to the ones published by Santos et al (2005) for different vegetable oils. In the same way, the viscosity of buriti oil was comparable to the values found by Ribeiro et al (2017) for different commercial olive oils. These olive oils had a very similar fatty acid composition to buriti oil, which also resulted in close agreement between buriti and olive oil densities.…”
Section: Physicochemical and Thermophysical Analysessupporting
confidence: 84%
“…However, it should be highlighted that, particularly for the refractive index and relative density, the observed variations of these physical properties were very low; in some cases, this was in the order of magnitude of the analytical device used, and thus monitoring their decrease is less useful from a practical point of view, if not even misleading. The viscosity values of oil samples stored up to 3 years were similar to those reported in other studies, 21,36,37 although a significant increase of viscosity was observed during storage. Previous studies have shown that olive oil undergoes an increase in viscosity during repeated frying operations 38,39 or after prolonged heating, such as in the case of treatments at 65 ∘ C for 45 days 40 or at 90 ∘ C for 35 days 41 .…”
Section: Resultssupporting
confidence: 89%
“…The viscosity values of oil samples stored up to 3 years were similar to those reported in other studies, although a significant increase of viscosity was observed during storage. Previous studies have shown that olive oil undergoes an increase in viscosity during repeated frying operations or after prolonged heating, such as in the case of treatments at 65 °C for 45 days or at 90 °C for 35 days.…”
Section: Resultsmentioning
confidence: 99%
“…Density also reflects the capacity for thorough homogenization of powder mixtures [15], which is crucial when dealing with milk powder [16], for example. Determining the correlation between density and viscosity can provide ready-to-use data, as well as important information that can be used to assess the quality of vegetable oils [17,18]. When dealing with foams, density is also indicative of air incorporation and, thus, foam stability with the aim of drying, but it can also be used for various other food and culinary applications [19].…”
Section: Density (ρ)mentioning
confidence: 99%